CO2 CAPTURE AND STORAGE IN PORTUGAL A BRIDGE TO A LOW CARBON ECONOMY - Seixas, Júlia (2016)
Current projections indicate that further efforts are required at national and EU level to keep the EU on track towards its new 2030 targets, and cut EU's greenhouse gas emissions by 80 to 95 % by 2050, as its longer term objectives to decarbonise the European energy and industry system in line with global climate stabilization achievement. This study shows how low carbon technologies interplay up to 2050 to achieve aggressive mitigation targets in Portugal, under diverse scenarios conditions. While power generation appears to become increasingly supported by renewables and energy efficiency, intensive industry should consider CCS for deep CO from industrial processes. As soon as private companies and public policy bodies identify the needs and opportunities from adopting CCS, while taking current uncertainty, the higher the chance to prevent competitive losses while bridge Portugal to a carbon constrained economy.